The Evaluation of Impact of Cable Power Lines on the Environment - M. A. Korotkevich; S. N. Azarov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The thermal impact of cable power lines and structural materials of cables on the environment has been considered. A quantitative evaluation of the thermal impact of electrical cables with cross-linked polyethylene insulation on the environment was carried out using the Elcut program. Analysis of the temperature field near the loaded cable line of 10 kV demonstrated high values of soil temperature that negatively affects its redox potential and living organisms. To evaluate the environmental impact of electrical cable materials, an approach has been developed that takes into account not only the toxicity of the materials but also their volumetric content in the cable. Cable lines with cables with traditional paper-oil insulation cause more damage to the environment than cable lines with cables, insulated with crosslinked polyethylene. The environment, in turn, also has an impact on the electrical cables: the values of long-term permissible load currents depend on the ambient temperature (when laying cables in the open air, in an earthen trench or in cable rooms). The impact of solar radiation on the thermal conditions of the electric cable is estimated. A comparative analysis of the complex environmental impact of electric cables with traditional insulation and insulation of crosslinked polyethylene demonstrated that unarmored cable with crosslinked polyethylene insulation at a voltage of 10 kV (regardless of the type of its shell) causes less damage to the environment than the same traditional cable throughout the considered temperature range on their surfaces.